Effects of the shear lag on longitudinal strain and flexural stiffness of flanged RC structural walls - Zhang, Zhongwen (2020)
The shear lag effect is a commonly reported observation in tests on flanged reinforced concrete (RC) structural walls. This effect is conventionally ignored but more evidence has shown that calculation and analyses ignoring this effect could significantly overestimate flexure strength and stiffness. Existing research indicates that well distributed diagonal cracks exist in the flange of the flanged RC walls with the shear lag effect and the effect should be calculated based on shear stiffness of the cracked concrete. A truss model was proposed but the model can only consider the effect at the bottom sections of cantilever flanged walls loaded at the top which therefore precludes its application in the design of flanged RC structural walls. This paper presents an improved truss analogy for calculating the shear lag effect for flanged section at any height of RC walls with any lateral load distributions. Predictions of the proposed method are compared with available experimental data and finite element (FE) results. The method is then applied to improve the fibre beam-column element models to generate a new prediction model which was found to predict to be able to accurately predict the flexure stiffness of RC walls.